PROFIL PEMECAHAN MASALAH MATEMATIKA SISWA KELAS XI MAN 1 PALU PADA MATERI BARISAN DAN DERET DITINJAU DARI GAYA BELAJAR - Sari, Nurhalisa Fitra; Ismaimuza, Dasa; Rochaminah, Sutji (Jurnal Elektronik Pendidikan Matematika Tadulako, 2022)
This study aims to describe the mathematical problem solving of class XI students of MAN 1 Palu on the material of sequences and series in terms of learning styles. The subjects in this study were three students of class XI MAN 1 Palu with visual, auditory and kinesthetic learning styles. The results of this study indicate that (1) the subject of visual learning style understands the problem by writing neatly and mentioning the information that is known and asked from the question, SV makes a problem-solving plan using existing information and knowledge of sequences and series, SV does not implement a problem-solving plan, can only get the value of the second term and do not know how to find the value of another term, SV does not re-check the answer. (2) subjects with auditory learning styles understand the problem by reading the questions repeatedly aloud but the SA is not good at understanding the questions because they are still wrong in writing the known information, the SA makes a problem-solving plan using existing information and knowledge of sequences and series, the SA carries out the plan troubleshooting but an error occurred in the end result, SA did not recheck the answer. (3) Subjects with a kinesthetic learning style understand the problem by practicing using their hands and then writing and mentioning the information that is known and asked from the problem, SK makes a problem-solving plan using existing information and knowledge of sequences and series, SK implements a problem-solving plan properly and correctly, SK rechecked the answers